2017
DOI: 10.1007/s10750-017-3144-0
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary prey facing an acute predation risk: testing the hypothesis of inducible metabolite emission suppression in zebra mussels, Dreissena polymorpha

Abstract: It takes time before a defensive phenotype can be effectively developed, which handicaps sessile bivalves exposed to acute predation risks. In a laboratory experiment, we examined whether predation threats induce zebra mussels to limit metabolic rates, serving as a fast-response defence that reduces the chances of chemical detection by predators. We measured the respiration rate of mussels exposed to predation treatments (fish fed zebra mussels, fish fed chironomids, crushed zebra mussels) and to predationfree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
5
16
1
Order By: Relevance
“…Contrary to our fourth hypothesis, we found no effect of chemical cues on metabolic rates of all three intermediate predators. However, our result contrasts with previous studies that reported elevated metabolic rates under predation risk in tadpoles (Steiner & Van Buskirk, 2009), grasshoppers (Hawlena & Schmitz, 2010b), spiders (Okuyama, 2015), bivalves (Antoł et al, 2018), and damselflies (Culler et al, 2014). However, our result contrasts with previous studies that reported elevated metabolic rates under predation risk in tadpoles (Steiner & Van Buskirk, 2009), grasshoppers (Hawlena & Schmitz, 2010b), spiders (Okuyama, 2015), bivalves (Antoł et al, 2018), and damselflies (Culler et al, 2014).…”
Section: Effects Of Predation Risk On Metabolic Ratescontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our fourth hypothesis, we found no effect of chemical cues on metabolic rates of all three intermediate predators. However, our result contrasts with previous studies that reported elevated metabolic rates under predation risk in tadpoles (Steiner & Van Buskirk, 2009), grasshoppers (Hawlena & Schmitz, 2010b), spiders (Okuyama, 2015), bivalves (Antoł et al, 2018), and damselflies (Culler et al, 2014). However, our result contrasts with previous studies that reported elevated metabolic rates under predation risk in tadpoles (Steiner & Van Buskirk, 2009), grasshoppers (Hawlena & Schmitz, 2010b), spiders (Okuyama, 2015), bivalves (Antoł et al, 2018), and damselflies (Culler et al, 2014).…”
Section: Effects Of Predation Risk On Metabolic Ratescontrasting
confidence: 99%
“…This response is consistent with previous studies showing that odonate predators respond primarily to visual predation risk stimuli (Corbet, 2004;Crespo, 2011). However, our result contrasts with previous studies that reported elevated metabolic rates under predation risk in tadpoles (Steiner & Van Buskirk, 2009), grasshoppers (Hawlena & Schmitz, 2010b), spiders (Okuyama, 2015), bivalves (Antoł et al, 2018), and damselflies (Culler et al, 2014). Our experimental method for producing the chemical cues was comparable to those used in other studies investigating the effect of predation risk (Brönmark & Hansson, 2012).…”
Section: Effects Of Predation Risk On Metabolic Ratessupporting
confidence: 90%
See 2 more Smart Citations
“…These papers cover a wide variety of topics, from a review of ecosystem services provided by freshwater mussels (Vaughn, 2017) to papers describing the diversity patterns and conservation of Unionida in East and Southeast Asia (Zieritz et al, 2017) as a result of international collaboration. Seven papers focus on different biological aspects of invasive bivalve species, including diversity changes by species substitution , physiological aspects (Labecka & Domagala, 2016), dispersion (Collas et al, 2016), ecological effects on native bivalve species (Ferreira-Rodríguez et al, 2016), low palatability to distinct predators (Castro et al, 2017), metabolite emission suppression in zebra mussels exposed to predation stress (Antoł et al, 2017) and the use of a new sonar technology and underwater imagery analysis for the survey of FB in rivers (Mehler et al, 2016). Propagation as a conservation tool was the subject of three studies: one about an improved method of in vitro culture of glochidia (Ma et al, 2016), one introducing short-term breeding of the Endangered freshwater pearl mussel Margaritifera margaritifera (Linnaeus, 1758) as a new technique for the augmentation of declining populations (Moorkens, 2017) and one revising the challenges in the conservation progress of Margaritifera auricularia (Spengler, 1793) .…”
Section: The Proceedings Of the Second International Meeting On Biolomentioning
confidence: 99%